Rice Husk Ash-Derived Magnetized Silica Functionalized with TMPDT for Heavy Metal Ion Removal - Hastuti, Sri; Irfani, Hasna Haifa; Nuzula, Rifania Aura; Saraswati, Teguh Endah; Masykur, Abu; Purnawan, Candra; Wibowo, Atmanto Heru; Fitriana, Dina (Universitas Jenderal Soedirman, 2026)
ABSTRACT. The removal of toxic heavy metal ions from water remains a critical environmental challenge. In this study, a novel magnetized mesoporous silica adsorbent functionalized with N1-(3-trimethoxysilylpropyl) diethylenetriamine (Fe₃O₄@SiO₂@meso-SiO2@TMPDT), synthesized from rice husk ash, was developed for the adsorption of Cd(II) and Pb(II) ions. The characterization of the adsorbent by FTIR, SEM-EDX, and TGA confirmed the successful synthesis of magnetized and TMPDT-functionalized silica derived from rice husk ash (Fe₃O₄@SiO₂@meso-SiO₂@TMPDT). The adsorption study consists of the determination of optimum pH, the adsorption kinetics study, and the adsorption isotherm. Batch adsorption studies showed that the optimal pH values for Cd(II) and Pb(II) adsorption were 4 and 3, respectively. The adsorption kinetics for both metal ions followed a pseudo-second-order model. Furthermore, the adsorption isotherms fitted both the Langmuir and the Freundlich models with comparable R² values. The maximum adsorption capacities (Qₘ) of Fe₃O₄@SiO₂@meso-SiO₂@TMPDT for Cd(II) and Pb(II) were 28.089 and 24.498 mg/g, respectively. These findings demonstrate that the developed adsorbents offer an effective and sustainable approach for heavy metal removal from aqueous systems. Keywords: adsorption, heavy metal ions, magnetized silica, rice husk ash, TMPDT